Effects of additives on the mechanical performance in recycled mixtures with bitumen emulsion: An overview. (30th July 2018) - Ayar, Pooyan
Highlights: Effects of additives on the mechanical performance in Recycled Mixture with Bitumen Emulsion (RMBE) have been reviewed. Fatigue response of RMBE containing cement could be affected by strain levels. The use of modified bitumen emulsion could improve rutting resistance of RMBE. Waste pozzolan can be used as a substitute for traditional additives in RMBE. The mechanisms of interaction between lime and bitumen emulsion need more clarification. Abstract: Cold recycling technology has been recognized as an efficient, cost-effective, and environmentally friendly method to rehabilitate asphalt pavements. Based on previous experiments, some solutions such as using additives (e.g. cement, lime, and waste pozzolans) and modifying bitumen emulsion have been proposed to enhance the performance, as well as to improve the sustainability of Recycled Mixture with Bitumen Emulsion (RMBE) as a cleaner product. Although some studies have evaluated the laboratory protocols to design RMBEs, there still remain many unclear issues related to the use of additives. Therefore, this article tries to review the general criteria for additive selection, and also to assess the different functional aspects of RMBEs (e.g. physical, durability and mechanical characteristics), paying attention to the impacts of additives. Additionally, key points concerning the use of modified bitumen emulsion in RMBEs were assessed. Finally, a series of important lines for further investigations in this field have been presented.